Plato's Minos: The Soul of the Law. Issue 3 (12th July 2016) - Davis, Michael
Abstract: The account of law in Plato's Minos is on its surface strange. Law is both what "wants to be the finding out of what is" and "the finding out of what is." It is a faculty in us like sight or hearing, and its stability requires that it be independent of us. It makes universal claims but always does so for a particular people in a particular place. Law must be grounded in what is beyond the law, and yet, once established, must assert its own final authority. Lawgivers must be at once above the law, almost a different species from those for whom they legislate, and, like everyone else, subject to the law. These ambiguities, indeed duplicities, are not so much defects of law to be resolved as indications of its fundamental nature. What follows is an account of this dual nature, especially in its necessary connection to poetry.